The Effect of Emotional Intelligence, Work-Family Conflict, Job Autonomy Company Performance: The Role Job Satisfaction and Job Stress as Mediating Variable - Rini Inthalasari; M. Arief (AIBPM Publisher, 2021)
The purpose of this study was to determine the effect of emotional intelligence, work-family conflict, job autonomy and company performance on job satisfaction mediated by job stress variables. The research approach used in this study is a quantitative approach. The object of this research is a property company in Tangerang City. The data in this study were distributed using a questionnaire technique through the G-Form. In this study, the exact number of the population is not known by the researcher. The sample in this study was selected by quota sampling technique. The data analysis used a structural approach to the Equation Model (SEM) assisted by the smart PLS application. The results of this study found that Emotional Intelligence has an effect on company performance, EI has no effect on performance mediated by job stress, job satisfaction is able to mediate ei's relationship to work stress, job autonomy has an effect on performance, job autonomy has an effect on company performance mediated by job stress, job autonomy has an effect on company performance mediated by job satisfaction, work family conflict has a significant negative effect on company performance, and job autonomy has an effect on company performance mediated by job stress.